Water masses and phytoplankton biomass distribution during summer in the Weddell Sea marginal ice zone - Pérez, Fiz F.; Tokarczyk, R.; Figueiras, F. G.; Ríos, Aida F. (Gauthier-Villars, 1994)
9 pages, 1 table, 6 figures This study - carried out between the Elephant and the Orkney islands - showed that spatial variability in the marginal ice-edge zone (MIZ) was greater than that found in open sea. Salinity and silicate contents point to the existence of two fronts: the first - near Elephant Island - separates the Surface Antarctic Water coming from Drake Passage from the winter water originating in the Weddell Sea. This water is characterized by its high concentrations of nitrate (> 30 mu M) and silicates (> 80 mu M). The second front - near the South Orkney Islands - undergoes the influence by a less saline water lens (< 34 %), poor in nutrients (N-NO3 < 24 mu M) and rich in chlorophyll (> 3.5 mg Chl a l super(-1)). Water masses circulation reveals the existence of a series of convergences and divergences which alternate along MIZ, together with different haline fronts. These fronts limit three different zones, taking into account the presence of chlorophyll. In zones where the surface layer presents both low salinity and stability with a thickness of about 40 m, chlorophyll contents are rather high - between 1.5 and 5 mg Chl a. m super(-3). On the other hand in the mixing vertical zone, these chlorophyll contents are low (<0.3 mg Chl a. m super(-3)) while the frontal region separating these two zones presents intermediate values and the existence of deep subsurface maximum of chlorophyll. Horizontal variability of integrated values (on the whole of the euphotic zone) is clearly inferior to the one present in surface concentrations. Peer reviewed